MDA-MB-231 breast cancer cells adapted to anchorage-independent growth reveal senescent-like phenotype and persistent downregulation of PD-L1 expression - Snedec, Tadeja; Repas, Jernej; Lah, Darin; Zemljič, Špela; Pavlin, Mojca (Frontiers in Oncology, 2025)
IntroductionMetastasis remains the primary cause of mortality in breast cancer, particularly in aggressive triple-negative (TNBC) subtypes. A crucial yet understudied aspect of this process involves cancer cell survival in a detached state and subsequent reattachment at distant sites. While in vitro models can capture early detachment events like tumor budding, the subsequent reattachment phase is often overlooked. To address this, we developed a TNBC cell model that effectively mimics metastatic behavior following re-attachment at secondary locations.MethodsWe generated clones of MDA-MB-231 TNBC cells through consecutive selection for enhanced anchorage-independent survival. This was achieved using 2-deoxy-D-glucose (2DG) alone, 2DG combined with metformin, or Poly(2-hydroxyethyl methacrylate) (polyHEMA)-coated surfaces. The resulting adapted clones were characterized by RNA transcriptomics, comparing them to one-time treated non-selected cells. Real-time cellular energy metabolism was assessed via Seahorse analysis, while mitochondrial mass and intracellular localization were determined by flow cytometry and fluorescent microscopy, respectively.ResultsTranscriptomic analysis of the MDA-MB-231 clones adapted to anchorage-independent growth revealed distinct alterations in gene expression, confirmed by principal component analysis showing clear separation from control clusters. These adapted clones exhibited increased mesenchymal and stemness markers, downregulated cell cycle genes, and a senescent-like phenotype. Interestingly, while nuclear-encoded oxidative phosphorylation (OxPhos) genes were downregulated, mitochondrial-encoded OxPhos genes were upregulated, with no significant shift in overall ATP production as measured by Seahorse analysis. Paradoxically, despite increased CD274 (PD-L1) transcription, surface PD-L1 expression was consistently reduced, likely due to endoplasmic reticulum (ER) stress and impaired N-glycosylation.DiscussionOur adapted clones provide a novel in vitro model of early metastatic behavior, unveiling a cancer cell survival strategy that balances energy metabolism with adaptation to stress. These clones also demonstrated enhanced detachment properties and upregulation of proto-oncogenes, in addition to their senescent-like phenotype. Critically, the uncoupling of CD274 transcription from surface PD-L1 expression suggests a potential therapeutic vulnerability that could be exploited in TNBC.